Computação em nuvem: tempos e espaços pedagógicos de aprendizagem colaborativa na educação profissional e tecnológica do Instituto Federal do Amapá - ARRELIAS, Josielson da Silva (2022)
The present study is an applied research that had objectified to stimulate the use of cloud computing by teachers and students of the high school integrated technical courses at the Instituto Federal de Educação, Ciências e Tecnologia do Amapá – IFAP, Campus Macapá. The project is inserted in the line of research organization and memories of pedagogical spaces in professional education and the master's degree in professional and technological education (ProfEPT) of the Federal Institute of Amapá, with investigative focus on the organization and planning of pedagogical spaces in the EPT (macro project 6), both in formal and non-formal spaces. The problem that guides the discussions is how cloud computing can resignify the spaces of professional education and technology (EPT), considering a collaborative education strand in cyberculture. The Study started with a survey to assess the knowledge and use frequency of the cloud computing technologies by teachers and students in the Integrated High School, followed by the application of an educational product in the form of a digital primer, with videos and examples of methodologies using the collaborative production tools of the Google's Workspace for education platform. According to the results, it is inferred that students and teachers already had contact with cloud computing tools and they have seasonally used them, nonetheless was observed a need of training courses for the use of these technologies by the teachers’ students surveyed. There is a potential for expanding the use of such tools by the school community, provided that training takes place and that teachers encourage their use.